2022
DOI: 10.1037/ppm0000296
|View full text |Cite
|
Sign up to set email alerts
|

Who finds media violence funny? Testing the effects of media violence exposure and dark personality traits.

Abstract: The popularity and commercial success of electronic media that pair humor with violence suggests that many people enjoy laughing at screen media violence. But who is most likely to find media violence funny? To answer this question, we measured media violence exposure, dark personality traits, and the extent to which participants found media violence humorous in 2 cross-sectional survey studies with samples of undergraduate students (Study 1 N = 215; Study 2 N = 178). Across the 2 studies, we assessed moral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Given that attitudes toward celebrity bashing are measured based on a combination of components, this study adds that this impact is not limited to perceptions of fairness but also contains elements of seeing it as harmless and entertaining. This positive association is attributed to the fact that moral disengagement helps suppress moral feelings, which increases the joy and acceptability toward antisocial behavior (Allen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that attitudes toward celebrity bashing are measured based on a combination of components, this study adds that this impact is not limited to perceptions of fairness but also contains elements of seeing it as harmless and entertaining. This positive association is attributed to the fact that moral disengagement helps suppress moral feelings, which increases the joy and acceptability toward antisocial behavior (Allen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Allison et al (2020), for instance, indicated that moral disengagement is associated with higher perceptions of fairness of aggression toward celebrities. Due to moral disengagement strategies, one is more flexible in interpreting antisocial behavior as acceptable and even as funny (Allen et al, 2021). Moreover, moral disengagement may increase under regular exposure to media violence, as one can practice with techniques of suppressing moral feelings (Allen et al, 2021;Teng et al, 2017).…”
Section: Moral Disengagementmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggests that this might be the case. Allen, Ash and Anderson ( 2021 ) found that dark triad personality traits like psychopathy (which includes antisocial behavior) were associated with enjoyment of a movie clip featuring aggressive humor. The authors suggest that related traits, such as an individual’s aggressive tendencies, might also be associated with liking humorous aggressive content (Allen, Ash & Anderson, 2021 ).…”
Section: The Co-development Of Aggression and Humor Type Preferencesmentioning
confidence: 99%
“…This argument is also supported by Bowes and colleagues (2018), who further noted that the impact of the socially aversive personality traits on everyday interests is scarcely understood. In fact, it is only recently that attempts have been made to understand how people with “darker” personalities respond to media narratives (Allen et al, 2021; Appel et al, 2019) and whether they deliberately select media to match their personal dispositions (e.g., Blagov et al, 2019). Still others have argued that the study of the associations between personality and preferences within media has tended to be dominated by research in the area of music (Rentfrow et al, 2011).…”
mentioning
confidence: 99%